A Community-Based Model to the COVID-19 Humanitarian Crisis - Nacoti, Mirco; Ciocca, Andrea; Brambillasca, Pietro; Fazzi, Francesco; Pisano, Michele; Giupponi, Massimo; Pesenti, Antonio; Valoti, Oliviero; Cereda, Maurizio (Frontiers in Cellular and Infection Microbiology, 2021)
A multidisciplinary group, mainly from Bergamo region - the epicenter of the COVID-19 pandemic crisis in Italy on march 2020– has developed concept of creating intermediate care facilities and proposes a three-tier model of community-based care, with the goal of reducing hospital admissions, contagion and mortality related to hospital overloading and optimizing human resources.